Inscription from Thomas Fitzgerald captive in Beauchamp Tower - Unknown (Tufts Archival Research Center, 2005)
This illustration is from the plate "Plan, View, and Inscriptions - Beauchamp Tower" in the History and Antiquities of London, Westminster, Southwark and parts adjacent, Vol. 2, by Thomas Allen.